(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2022)
Division Bench of Bombay High Court relying a case pronounced by Hon’ble SC, and observed that this would enable us to hold that on the three parameters of Jacob Mathews vs. State of Punjab and another, 2005 ALL MR (Cri) 2567 (SC) namely: duty to take care, breach of duty and consequential damage, this case fails to attract any criminal offence, much less offence of culpable homicide not amounting to murder. Division Bench of Bombay High Court clarified that in recording such a finding, we have only considered the criminal dimension of the case insofar as it relates to the petitioner and we have not dealt with civil dimension of the case involving such issues as of damages, civil liability, departmental action and so on, in any manner. Bench further observed that it is, thus, apparent that there is absolutely no material available on record showing, prima facie, that offence of culpable homicide not amounting to murder punishable under Section 304 of I.P.C. is constituted against the present petitioner. Continuation of these proceedings against the present petitioner, in the present circumstances, would clearly be an abuse of process of law, which cannot be permitted. In the instant case, considering the allegations as levelled against the petitioner, of his absence in the NICU at the relevant time, would, even if everything as mentioned in the charge sheet was presumed to be true, at the most, may lay a blame of dereliction of duty at his doorstep, for which Departmental action can always be taken by the authorities, as has been reported to have been done in the case of Professor and Head of Department of Paediatrics, who was absent without sanctioned leave on the fateful day. The Division Bench of Bombay High Court concluded that the material in the charge-sheet was certainly not indicative of the petitioner having prima facie committed an offence under Section 304 of I.P.C. Bench, thus, of the view that continuation of the proceedings against the petitioner would clearly be an abuse of the process of law, which would always be unsustainable in law. In the circumstances, the charge-sheet No.278/2017 for the offence under Section 304 read with Section 34 of IPC as against the present petitioner is quashed and set aside. This Research Paper deals with critical appraisal of a case of alleged criminal medical negligence, insight into criminal and civil dimensions of the case and duty of nurse-in-charge of NICU, duty of doctors and need for protocol, SOP in preventing such unfortunate incident in future.